Malay Mail, 11 June 2009 (The New Straits Times Press (M) Bhd, 2009)
The World Health Organisation is gathering up to declare an H1N1 pandemic, a move that could trigger both the large-scale production of vaccine and questions about why the step was delayed for weeks as the virus continued to spread.